(untitled) (Eurasian Journal of Philology Science and Education, 2015)
The article deals with the means of expression of SMS language in the English and Russian languages:the use of transliteration, reductions and symbols. SMS communication is a new kind of interpersonal communication that contributed to the emergence of new concepts in our life, which led to the formationof a large number of neologisms and mainly telescopic units. The main features of SMS messaging as a genre are brevity, immediacy and the private (non-public) character of the content, a strong dependence on information transmission medium – the mobile phone which allows only the small volume of the message and has a limited set of keys. SMS communication takes an intermediary place between the written and spoken language. Being considered as a written form, it has bright signs of colloquialism. SMS sublanguage is characterized by certain unique set of lexical, grammatical and semiotic characteristics that are easily categorized and systematized.